Itraconazole Prophylaxis for an Outbreak of Invasive Aspergillosis in a Hematology Ward after Hospital Construction Work - Hirayama, Yasuo; Terui, Takeshi; Kamihara, Yusuke; Iyama, Satoshi; Takada, Kohichi; Murase, Kazuyuki; Sato, Tsutomu; Kobune, Masayoshi; Kato, Junji; Ishitani, Kunihiko (Journal of Hematology and Oncology Research, 2015)
Objective: Hospital construction work, among other environmental factors, is a risk factor for invasive aspergillosis (IA). Methods: We retrospectively surveyed the incidence of IA in hematology-oncology patients before and during hospital construction and studied the effectiveness of prophylactic oral itraconazole (ITCZ) treatment. We compared the rates of galactomannan (GM)-positive cases and probable IA cases among 224 patients discharged before the start of construction work and among 67 patients hospitalized within two months after the start of the construction work. Results: Our results showed that, during the 12 months before the construction work was started, only four patients were GM-positive, and one had a probable diagnosis; in contrast, among patients hospitalized within two months from the start of the construction work, seven patients were GM-positive, and four had a probable diagnosis. Therefore, we started to administer oral ITCZ to 40 patients with hematological diseases. Although the construction work continued, after the ITCZ prophylaxis, no new probable cases of IA were detected. Conclusion: From our experience, GM surveillance among hematological patients is necessary during hospital construction work, and the administration of ITCZ to prophylactically prevent IA is suggested upon detection of an increase in GM-positive patients.
Keywords: galactomannan; invasive aspergillosis; construction; prophylaxis; itraconazole